Termination of pregnancy in preserving the Maqasid Shariah concept of life – case series - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Emmaculcate Tiko, Victoria (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2021)
Termination of pregnancy (TOP) is indicated for the sake of saving the life of a pregnant woman in the best clinical judgement of the treating doctor. This is in line with what recommended in the al-Quran and according to the expert opinion of Islamic and Medical scholars. However, this could be a dilemma for most medical doctors in handling pregnant mothers who are in emotional distress due to the unplanned pregnancy or premarital conception, in which how far should we agree to the TOP request. This case series aims to highlight this issue. We would like to share case series on two related cases of mothers who had features of depression secondary to unplanned and unwanted pregnancy. Both mothers requested TOP with hopelessness, sadness, anhedonia, reduced appetite and sleep, and feeling low and down. Rather than directly channel this case for TOP in the tertiary centre, we approached this case with motivational interview and psychological support in which close follow-up had been done at the primary care level. The first mother benefited from the counselling and managed well with some antidepressants and psychotherapy. With family support and open discussion, the patient finally recovered from their acute stress condition and decided to take care of the pregnancy rather than proceed with the TOPs. Another case was referred for TOP after our adequate assessment in view of worsening emotional distress. However, her request was denied by a treating Obstetrician. She ends up with self-abortion and sepsis. The need for TOP in psychological distress is still debatable. Monitoring and follow up in primary care setting have become an important assistance tool in managing these cases. It gives ample time for the mother and treating doctors to understand the situation thoroughly before deciding to terminate the foetus’s life, which might be unnecessary. However, failure to look at the case from the “Maqasid Shariah” concept on life and mind will lead to unnecessary action by the patient and loses her life